TEACHING UZBEKISTAN FOLK EPISTLES ON THE BASIS OF COMPARATIVE ANALYSIS METHODS - Anisbekova Dilfuza Makhammadumar qizi (Sciental Journals Publishing, 2025)
This article covers the theoretical and practical aspects of using comparative analysis methods in the study and teaching of Uzbek folk epics. Epics, which are unique examples of folk oral art, serve as an important source for understanding national identity, restoring historical memory, and educating the younger generation. The method of comparative analysis makes it possible to reveal their common and specific features by comparing epics with other folk epic heritage. The article discusses the methodology for analyzing epics in terms of cultural, ideological, and artistic aspects in the process of teaching, as well as the problems and solutions of their integration into modern education.